Strategy for Selective Middle Hepatic Vein Reconstruction in Living Donor Liver Transplantation Using Right Lobe Graft - 홍성연 (The Graduate School, Ajou University, 2021)
AIM: To verify the safety and feasibility of our selection criteria for middle hepatic vein (MHV) reconstruction in living donor liver transplantation (LDLT) using right lobe graft. METHODS: A total of 153 LDLTs were performed using right lobe grafts in a tertiary hospital from 2006 to 2016. Among them, 52 cases without MHV reconstruction were compared with 101 recipients who underwent LDLT using right lobe graft with MHV reconstruction. Both groups were compared regarding indications for reconstruction, short-term and long-term complications, operative details, and outcomes. RESULTS: Two groups differed only in cold ischemic time (108.19 49.81 minutes versus 146.37 58.74 minutes) preoperatively. Short-term post-transplant outcomes, long-term overall survival, and long-time disease-free survival showed no significant differences between the two groups. After propensity score matching for both groups with and without MHV reconstruction to annihilate selection bias, the two groups were comparable. CONCLUSION: We found that our selection criteria for performing MHV reconstruction in LDLT using right lobe graft were feasible and safe. A routine MHV reconstruction is not necessary if the RL graft GRWR was greater than or equal to 1.0, RHVV greater than or equal to 0.8, and recipient MELD score less than 20.
학위논문(석사)--아주대학교 일반대학원 :의학과,2021. 8
Keywords: Liver transplantation; graft congestion; hepatocellular carcinoma; middle hepatic vein; vascular reconstruction